THE INFLUENCE ANALYSIS OF ORGANIZATIONAL CLIMATE AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE THROUGH HAPPINESS AT WORK AS MEDIATION VARIABLE - Adinda Hayyu Rizqi; Ika Nurul Qamari (Journal of Management and Islamic Finance, 2022)
This study discusses the influence of Organizational Climate and Work-life Balance on Employee Performance through Happiness at Work as Mediation Variable at the Sinduadi Village office. The number of samples in this study were 105 employees. The data collection technique for sampling used simple random sampling by applying the questionnaire method. The analytical method used the Structural Equation Modeling (SEM) method processed through the AMOS 22 program. The results of this study indicate that Organizational Climate has positive effect but is not significant on Employee Performance, Organizational Climate has a positive effect on Happiness at Work, Happiness at Work has a significant positive effect on Employee Performance, Work-life Balance has a significant positive effect on Employee Performance, Work-life Balance has a significant positive effect on Happiness at Work, Organizational Climate has a significant effect on Employee Performance through Happiness at Work, Work-life Balance has a significant positive effect on Employees Performance through Happiness at Work.